STUDIES ON DIGESTIVE ORGANS OF TWO SEA TURTLES, Chelonia mydas L. and Eretmochelys imbricata L. - I Nyoman S. Nuitja; Silvia Wijaya (Indonesian Fisheries Research Journal, 2005)
The digestive organs of two sea turdes, Chelonia mydas L. and Eretmochelys imbicata L. with purpose to analyse the digestive tract and other organs, also to preform their weight were carapace length relation skimp. The specimens of the two species were obtained from slaughtered houses in Benoa Bay, South Bali.